2021
DOI: 10.3390/pollutants1010002
|View full text |Cite
|
Sign up to set email alerts
|

The Appropriateness of Using Aquatic Snails as Bioindicators of Toxicity for Oil Sands Process-Affected Water

Abstract: Canada’s oil sands mining activity produces large volumes of oil sands process-affected water (OSPW), and there have been increasing concerns regarding the potential environmental impacts associated with this material. Developing an understanding of the toxicity of OSPW is critical to anticipating and mitigating the potential risks and effects of the oil sands industry on surrounding ecosystems. The composition of OSPW is highly variable and is influenced by a range of factors. While numerous research projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, MT induction in aquatic species brought on by ambient exposure to heavy metals is more difficult to detect in field investigations, because environmental variables are less well characterized than in laboratory research [ 35 ]. Choosing a suitable organism to serve as a bioindicator is crucial [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MT induction in aquatic species brought on by ambient exposure to heavy metals is more difficult to detect in field investigations, because environmental variables are less well characterized than in laboratory research [ 35 ]. Choosing a suitable organism to serve as a bioindicator is crucial [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Cu is important for MT biosynthesis due to significant correlation more than Ni, Cr, Cd and Hg. A possible justification for the findings is related to that Cu is an essential trace metals and MT play a major role in its hemostasis in crabs [ 36 ]. Also, Cu was reported to promote MT synthesis in different tissues, such as digestive gland and gills of mussels [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in field studies, where environmental circumstances are less well defined than in laboratory research, MT induction in aquatic species caused by environmental exposure to heavy metals is more difficult to assess [Linde et al, 2001]. Therefore, the choice of an appropriate organism as bioindicator is important [Chen et al, 2021].…”
Section: Introductionmentioning
confidence: 99%